2021
DOI: 10.20944/preprints202104.0022.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunomodulation as a Potent COVID-19 Pharmacotherapy: Past, Present and Future

Abstract: In the first year of its appearance, the 2019 coronavirus disease (COVID-19) has affected more than 120 million individuals and killed 2 million people worldwide. The pandemic has also triggered numerous global initiatives to tackle the newly emerging disease, including the development of SARS-CoV-2 vaccines and the attempt to discover potential pharmacological therapies. Nonetheless, despite the success of SARS-CoV-2 vaccines development, the COVID-19 therapy remains challenging. Several repurposed drugs that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The four molecules associated only with mild COVID-19 included cereblon (CRBN), hemoglobin (HBA)1/HBA2, JAK2, and tumor necrosis factor ligand superfamily member 11 (TNFSF11) (Table 1). Moreover, while only one chemokine/cytokine molecule was found to be associated with mild COVID-19, 15 chemokine/cytokine molecules were found to be associated with severe COVID-19 in QKB, which is consistent with the evidence of cytokine storm worsening the prognosis of COVID-19 [69], and the call for immunologic treatments in severe COVID-19 cases but not in mild COVID-19 cases [69]. It would be helpful to identify molecular profiles specific for mild and severe COVID-19, respectively, and use this molecular profile to facilitate the diagnosis and design of therapeutic interventions including immune modulation.…”
Section: Discussionsupporting
confidence: 79%
“…The four molecules associated only with mild COVID-19 included cereblon (CRBN), hemoglobin (HBA)1/HBA2, JAK2, and tumor necrosis factor ligand superfamily member 11 (TNFSF11) (Table 1). Moreover, while only one chemokine/cytokine molecule was found to be associated with mild COVID-19, 15 chemokine/cytokine molecules were found to be associated with severe COVID-19 in QKB, which is consistent with the evidence of cytokine storm worsening the prognosis of COVID-19 [69], and the call for immunologic treatments in severe COVID-19 cases but not in mild COVID-19 cases [69]. It would be helpful to identify molecular profiles specific for mild and severe COVID-19, respectively, and use this molecular profile to facilitate the diagnosis and design of therapeutic interventions including immune modulation.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the choice of antiarrhythmics for patients who develop AF during infections is still an open debate, although some potentially relevant prognostic differences were outlined recently [ 71 , 72 ]. Ultimately, the role of immunomodulating therapies in this clinical scenario is still unclear and needs further specific investigation [ 73 ]. From a broader perspective, as AF occurring during COVID-19 may indicate increased clinical complexity, these patients should be carefully evaluated for the presence of other clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher mean Vi PLUS value was found in COVID-19 patients with pulmonary injury (1.74 ± 0.28 vs. 1.64 ± 0.25, p < 0.0009) in our study. While inflammation plays a pivotal role in the development and progression of liver fibrosis, the non-invasive assessment of inflammation has been studied in past years, with promising results [ 32 , 33 , 34 , 35 , 36 , 37 ]. Several preliminary studies have shown that viscosity might be a useful parameter in tissue characterization, and it might help to detect necroinflammation in the liver [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%